The forty years of vermicular graphite cast iron development in China (Part Ⅲ) - QIU han-quan; CHEN Zheng-de (China Foundry, 2007)
In China, the research and development of vermicular graphite cast iron (VGCI) as a new type of engineering material, were started in the same period as in other developed countries; however, its actual industrial application was even earlier. In China, the deep and intensive studies on VGCI began as early as the 1960s. According to the incomplete statistics to date, more than 600 papers on VGCI have been published by Chinese researchers and scholars at national and international conferences, and in technical journals. More than ten types of production methods and more than thirty types of treatment alloy have been studied. Formulae for calculating the critical addition of treatment alloy required to produce VGCI have been put forward, and mechanisms for explaining the formation of dross during treatment were brought forward. The casting properties, metallographic structure, mechanical and physical properties and machining performance of VGCI, as well as the relationships between them, have all been studied in detail. The Chinese Standards for VGCI and VGCI metallographic structure have been issued. In China, the primary crystallization of VGCI has been studied by many researchers and scholars. The properties of VGCI can be improved by heat treatment and addition of alloying elements enabling its applications to be further expanded. Hundreds of kinds of VGCI castings have been produced and used in vehicles, engines, mining equipment, metallurgical products serviced under alternating thermal load, machinery, hydraulic components, textile machine parts and military applications. The heaviest VGCI casting produced is 38 tons and the lightest is only 1 kg. Currently, the annual production of the VGCI in China is about 200 000 tons. The majority of castings are made from cupola iron without pre-treatment, however, they are also produced from electric furnaces and by duplex melting from cupolaelectric furnaces or blast furnace-electric furnace. Examples of typical applications for VGCI castings are introduced in this paper. In China, the technologies such as rapid testing of the molten metal and non-destructive testing of casting microstructure still need to be improved. Several proposals are put forward in this paper in order to improve the production of VGCI. Generally speaking, in China, the research, production, and application of vermicular graphite cast iron are at the same level as in other developed countries and in some fields China even takes lead. (332 references and 5 Tables)